Marketing Strategy Recommendation for Kiwang Kreatif Craft in Garut West Java - Didip Diandra, BA., MBA; Astra Novlantig (Management and Leadership Study Programme, 2018)
This research analyzes the marketing strategy of Kiwang Kreatif Craft (KKC) to optimize their business growth. The objectives of this study is to reveal the current marketing strategies that implemented by KKC and to recommend the advance marketing strategy to optimize their business performance.This research used qualitative research approach and exploratory method by interviewing the chairman of Kiwang Kreatif and its stakeholders. The result of analysis shows that the majority of promotional strategies are relatively still conventional. Others, KKC should implement internet marketing platform and social media as a media for promotion, then educate their members about what is and how to optimized the internet marketing platform, should improve the selling process become an offline and online mode, and should optimize the required physical evidence to improve their brand awareness.